2019
DOI: 10.1002/cbic.201900101
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Site‐Specific Antibody–Drug Conjugation by Engineering a Nature‐Derived Recognition Tag for Microbial Transglutaminase

Abstract: Microbial transglutaminase (mTG) has recently emerged as a powerful tool for antibody engineering. In nature, it catalyzes the formation of amide bonds between glutamine side chains and primary amines. Being applied to numerous research fields from material sciences to medicine, mTG enables efficient site‐specific conjugation of molecular architectures that possess suitable recognition motifs. In monoclonal antibodies, the lack of native transamidation sites is bypassed by incorporating specific peptide recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…19C). 289 An analysis of the substrate preference of mTG within a series of synthetic peptides derived from sequences within the papain inhibitor, as well as DAIP, was conducted. Anti-HER2 ADCs were assembled via recognition tags fused to the heavy chain C-termini, attachment with amino-PEG 2 -BCN linkers, followed by SPAAC with the azido-PEG 3 -Val-Cit-PABC-MMAE payload.…”
Section: Transglutaminasementioning
confidence: 99%
“…19C). 289 An analysis of the substrate preference of mTG within a series of synthetic peptides derived from sequences within the papain inhibitor, as well as DAIP, was conducted. Anti-HER2 ADCs were assembled via recognition tags fused to the heavy chain C-termini, attachment with amino-PEG 2 -BCN linkers, followed by SPAAC with the azido-PEG 3 -Val-Cit-PABC-MMAE payload.…”
Section: Transglutaminasementioning
confidence: 99%
“…[4] The site-specific conjugation [5] was clearly a major trend during the last years; nevertheless, a recent publication showed that heterogeneous stochastic conjugation can be beneficial over homogeneous site-specific conjugation. [5a] However, even modern site-specific conjugation procedures using, for example, genetically engineered amino acids or enzymatic approaches [6] mainly focus on the efficacy of the resulting ADCs or improvement of their pharmacokinetics/pharmacodynamics. Surprisingly, little attention is paid to the overall conjugation efficiency and manufacturability of the developed procedures.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 One such reaction is lysine (Lys) acylation, where Lys acetylation is critical for histones and in other contexts, [27][28][29][30] and many longer-chain Lys acylation PTMs [31][32][33] such as malonylation, 34,35 succinylation, 34,36 and glutarylation 37,38 have been discovered yet are poorly understood. 39 As an alternative to approaches that include introduction of Lys analogues, [40][41][42][43] nonsense codon suppression, [44][45][46][47][48][49] bottom-up ligation-based assembly strategies, [50][51][52] or enzymatic methods that typically require creation of a non-native protein by insertion of a specific target sequence, [53][54][55][56][57][58] DNAzymes are promising for top-down introduction of Lys acylation PTMs onto intact native proteins, [59][60][61][62][63][64][65] but only if DNAzymes can be identified with the fundamental catalytic ability of Lys acylation.…”
Section: Introductionmentioning
confidence: 99%